ORGANISATIONAL EFFICACY AND QUALITY OF SERVICES: THE ROLE OF EDUCATORS IN AN ITALIAN CASE STUDY (Fiep Bulletin - online, 2014)
The «Polisportiva Giovanni Masi» (PGM) has been analyzed for 3 years by our research group since 2010. The club, whichboasts more than 7000 members, is located in Casalecchio di Reno, a municipality of 38000 inhabitants near Bologna. The research, basedon the case-study approach (Yin, 2009) has been carried out with a special focus on the quality of the services, the level of satisfaction ofthe members, the organizational processes, questionnaires with members (n=1100), in-depth interviews (n=11), focus groups (n=9), lifehistories (n=4) and observations have been interpolated. Results show that PGM is recognized as a high quality organization. The mainfactors of the high degree of the members’ satisfaction for the provided services (very good=12,7%, good=77,6% of the respondent) arethe relationships with the sports educators/coaches/instructors - 50% of them holding a Physical Education or Sport Sciences degree- (verysatisfied=58,9%, satisfied=27,8%) and the assessment of their professional competences (very good=43,4%, good=40,7%). Data collected,which highlight as the success of the organization is, above all, linked to the quality of the didactics, are deeply rooted in the history ofPGM. In fact, it has been within the first associations to: propose psychomotricity classes in 1975, as well as baby swimming; invest in highquality training develop and adopt an educational internal code.PGM witnessed a process of professionalization as well as a trend thatmade communication and decisional procedures more complex. On the light of that, the monitoring carried out during the second and thirdyears of the study, shows that PGM reacted with the rationalization of the internal structure and organizational procedures and with theinvolvement of a more professionalized workforce.
Keywords: sport club; educators; organizational factors of success; multidimensional approach